Comparison of Sleep Quality in Kidney Transplant Recipients vs. Hemodialysis Patients: A Cross-Sectional Study - Marjan Shamspour; Najmeh Shamspour; Nazanin Kharazmi; Jalal Azmandian; Azam Dehghani; Mohamad Reza Zare (Journal of Sleep Sciences, 2023)
Background and Objective: Determining sleep quality in hemodialysis patients and kidney transplant recipients can provide valuable clinical information for planning treatment and care in this group of patients. Thus, we compared sleep quality between hemodialysis patients and kidney transplant recipients.